Corrigendum to “Extraction of notable points from ECG data: A description of a dataset related to 30-s seated and 30-s stand up”[Data in Brief, volume 46 (2023) 108874] - Duarte, Rui Pedro; Marinho, Francisco Alexandre; Bastos, Eduarda Sofia; Pinto, Rui João; Silva, Pedro Miguel; Fermino, Alice; Vitalyvna Denysyuk, Hanna; Gouveia, António Jorge; Gonçalves, Norberto Jorge; Coelho, Paulo Jorge; Zdravevski, Eftim; Lameski, Petre; et al. (Elsevier, 2023)
This work is funded by FCT/MEC through national funds and, when applicable, co-funded by the FEDER-PT2020 partnership agreement under the project UIDB/50008/2020. This work is also funded by FCT/MEC through national funds and, when applicable, co-funded by the FEDER-PT2020 partnership agreement under the project UIDB/00308/2020. Hanna Vitaliyivna Denysyuk is funded by the Portuguese Foundation for Science and Technology under scholarship number 2021.06685. BD